2017
DOI: 10.18632/oncotarget.23143
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF-κB prevents the acidic bile-induced oncogenic mRNA phenotype, in human hypopharyngeal cells

Abstract: Bile-containing gastro-duodenal reflux has been clinically considered an independent risk factor in hypopharyngeal carcinogenesis. We recently showed that the chronic effect of acidic bile, at pH 4.0, selectively induces NF-κB activation and accelerates the transcriptional levels of genes, linked to head and neck cancer, in normal hypopharyngeal epithelial cells. Here, we hypothesize that NF-κB inhibition is capable of preventing the acidic bile-induced and cancer-related mRNA phenotype, in treated normal huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
76
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(96 citation statements)
references
References 45 publications
20
76
0
Order By: Relevance
“…In line with our recent study,33 our current data suggest that NF‐κB inhibition may reverse acidic bile‐induced molecular events in normal human hypopharyngeal cells that are known to link inflammation to cancer, thereby in a sense shielding HHPC from the effects of bile‐induced oncogenic molecular events.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our recent study,33 our current data suggest that NF‐κB inhibition may reverse acidic bile‐induced molecular events in normal human hypopharyngeal cells that are known to link inflammation to cancer, thereby in a sense shielding HHPC from the effects of bile‐induced oncogenic molecular events.…”
Section: Discussionsupporting
confidence: 92%
“…We used the same pool of total RNA to determine, by qPCR, the effect of BAY 11‐7082 on transcriptional levels of RELA(p65), TNF‐α, IL‐1β, IL‐6 and STAT3 in acidic bile‐treated and control HHPC with or without BAY 11‐7082, as previously described33 (Supplementary Methods & Table S2). These genes were selected because they demonstrated an increased transcriptional activity under acidic bile exposure of HHPC 8, 9 that was prevented by BAY 11‐7082 in our previous study 33…”
Section: Methodsmentioning
confidence: 99%
“…Because PI3K activation may lead to downstream NF-κB activation, 35 its role in bile-induced NF-κB activation requires further exploration. 9,33,34,43,44 Bile(+) tumors also demonstrate an intense downregulation of tumor suppressors miR-489, miR-504, and miR-99a compared with their ANTs, a finding that is in keeping with previous studies suggesting their involvement in the initiation and progression of HSCC. 46,47 The data from the current study do not fully support a strong association between the NOTCH family and bile(+) HSCC.…”
Section: Discussionsupporting
confidence: 87%
“…7,32,33 Our analysis using qPCR demonstrated that bile(+) HSCC produced an upregulated NF-κB-related mRNA phenotype (Fig. 7,32,33 Our analysis using qPCR demonstrated that bile(+) HSCC produced an upregulated NF-κB-related mRNA phenotype (Fig.…”
Section: Upregulation Of Nf-κb-related Mrna In Hscc From Patients Witmentioning
confidence: 84%
See 1 more Smart Citation